Antioxidant behaviour of carotenoids highly accumulated in HepG2 cells - Jaswir, Irwandi; Kobayashi, Miyuki; Koyama, Toshie; Kotake-Nara, Eiichi; Nagao, Akihiko (Elsevier, 2012)
The antioxidant behaviour of major dietary carotenoids accumulated at high concentrations in human hepatoma HepG2 cells was evaluated, in comparison with a-tocopherol. The cells that accumulated carotenoids and a-tocopherol at levels higher than the values reported in the human liver were exposed to mild oxidative stress with tert-butylhydroperoxide. b-Carotene (>2.6 nmol/mg protein) and astaxanthin (>1.8 nmol/mg protein) significantly suppressed lipid peroxidation, while b-cryptoxanthin and lutein did not. a-Tocopherol remarkably suppressed lipid peroxidation with an IC50 value of 0.16 nmol/mg protein. Neither a-tocopherol nor any of the carotenoids except for lycopene showed pro-oxidant action even at high cellular concentrations. The antioxidant behaviours of carotenoids in a cellular milieu were quite different from those previously found in liposomes and homogeneous solutions. Further studies are required to assess the implications of the antioxidant behaviours found in the cultured cells on human health.